A Survey of the Matrix Exponential Formulae with Some Applications (Journal of Mathematical Study, 2021)
The matrix exponential formulae are very important tools in diverse fields ofmathematical physics, in particular, they are also useful in studying quantum informationtheory. In this paper, we survey results related to matrix exponential thoroughly. Thepurpose of the article is pedagogical.